The Potential of siRNA-Mediated Oncogene Silencing in Cancer Therapy: An Overview of Pharmacogenomics Strategies - Shanbhag, Preeti; Bhat, Ramdas; A R Shabaraya (Indian Journal of Pharmacy & Drug Studies, 2023)
siRNA-mediated silencing of oncogenes holds great promise as a potential cancer therapy. By selectively silencing genes involved in cancer progression, siRNA-based therapies have the potential to be highly specific and effective, while minimizing off-target effects and toxicity. However, several challenges need to be addressed before siRNA-based therapies can be widely used in clinical settings. One of the major challenges is the development of efficient and safe delivery systems for siRNAs. Additionally, more clinical trials are needed to evaluate the safety and efficacy of siRNA-based therapies for cancer treatment. Despite these challenges, ongoing research and development in the field of siRNA-based therapies are promising. New delivery systems, personalized medicine approaches, and combination therapies are being explored, which could potentially lead to more effective and personalized cancer treatment. With continued research and development, it is hoped that siRNA-based therapies will eventually become cancer treatments, providing patients with a more targeted and effective treatment option.